2018
DOI: 10.1098/rsos.171790
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leg-to-body ratio, arm-to-body ratio and intra-limb ratio on male human attractiveness

Abstract: Human mate choice is influenced by limb proportions. Previous work has focused on leg-to-body ratio (LBR) as a determinant of male attractiveness and found a preference for limbs that are close to, or slightly above, the average. We investigated the influence of two other key aspects of limb morphology: arm-to-body ratio (ABR) and intra-limb ratio (IR). In three studies of heterosexual women from the USA, we tested the attractiveness of male physiques that varied in LBR, ABR and IR, using figures that ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…In men specifically, evidence suggests that increased leg length relative to height is an intersexually selected cue of health (i.e., it is attractive to women; reviewed in Bogin & Varela-Silva, 2010;Sorokowski, 2010). Contrasting to this, women do not show a preference for men with longer arms relative to body length (Versluys, Foley, & Skylark, 2018). Analyses of skeletal remains suggests that arm length, particularly upper arm length, is not as sensitive to nutrition and disease as leg length is (Jantz & Jantz, 1999;Meadows & Jantz, 1995) which undermines its validity as a health cue.…”
Section: Discussionmentioning
confidence: 99%
“…In men specifically, evidence suggests that increased leg length relative to height is an intersexually selected cue of health (i.e., it is attractive to women; reviewed in Bogin & Varela-Silva, 2010;Sorokowski, 2010). Contrasting to this, women do not show a preference for men with longer arms relative to body length (Versluys, Foley, & Skylark, 2018). Analyses of skeletal remains suggests that arm length, particularly upper arm length, is not as sensitive to nutrition and disease as leg length is (Jantz & Jantz, 1999;Meadows & Jantz, 1995) which undermines its validity as a health cue.…”
Section: Discussionmentioning
confidence: 99%
“…Versluys et al have shown that AL is proportional to forearm length with an intra-limb ratio of 0.817, which suggest that upper AL may be used for a preoperative assessment of tibial nail length. 12 This study shows that AL had the least average difference to nail length for all observations made with narrow limits of agreement. On repeatability assessment using the BlandAltman method, we found that AL showed a difference of −0.02 mm on average when measured by different observers and the limits of agreement at −19.04 to 19.01, indicating good repeatability.…”
Section: Discussionmentioning
confidence: 55%
“…The ideal limb can allow a player to move more efficiently. The ideal leg-to-body ratio is at least 1:0.5 [10,11]. The ideal arm span and leg ratio are important requirements in determining talent in basketball.…”
Section: Introductionmentioning
confidence: 99%